The influence of indigestible protein on the performance and meat quality of broilers vaccinated for coccidiosis. (17th April 2019) - Bryan, D D L S; Abbott, D A; Classen, H L
ABSTRACT: High dietary protein and the use of poorly digested protein sources have been suggested to negatively impact broiler health, possibly because of protein fermentation in the distal intestinal tract. The effect of dietary protein levels with low or high indigestible protein fractions (LIP or HIP) on male and female broiler performance were evaluated. The trial was completely randomized with a 2 × 3 × 2 factorial arrangement, where gender, dietary protein levels (24, 26, and 28%), and dietary protein digestible fractions were the main factors. Ross 308 male (1944) and female (2232) were allocated to 72 pens with 54 males or 62 females per pen. Six grower diets 24-LIP, 24-HIP, 26-LIP, 26-HIP, 28-LIP, and 28-HIP were fed from 0 to 32 D of age. Birds were vaccinated with Coccivac-B52 on day 5, and feed intake and BW were recorded on 0, 12, 22, and 32 D. On day 32, 24 birds per treatment were processed for meat yield. Males were heavier than females at all post-hatch ages and the LIP birds were heavier than their HIP counterparts on 32 D. On day 22, birds fed 24 and 26% CP were heavier than those fed 28% CP. Birds fed the 28-LIP diet consumed less total feed than their 24 and 26-LIP equivalents. Birds fed 24% CP had the highest total feed to gain ratio, whereas LIP fed birds had a lower total feed to gain than those fed HIP diets. LIP diets resulted in higher total mortality than the HIP diets. Carcass yield was higher for females than males, increased with CP level, and was lower in HIP than LIP birds. An interaction between CP level and protein digestibility resulted in the 26 and 28-LIP having higher breast yield than all other diets. In conclusion, broiler growth performance and meat yield were affected by dietary indigestible protein alone or in combination with gender and dietary CP level.